Analytical Design Structure of New Segmental Stator Permanent Magnet Flux Switching Motor. Issue 1 (September 2020) - Othman, S.M.N.S.; Sulaiman, Erwan; Jenal, Mahyuzie
Abstract: Permanent Magnet Flux Switching Machines (PMFSM)s are among the most widely investigated types of electric motor because of high flux density compared to switch reluctance motor (SRM). The aim of the present work is to design a three phase 12Slot-14Pole segmental stator (SegSta) PMFSM and to investigate the flux linkage of U, V, W phase. In this study, 12S- 14P SegSta PMFSM is investigated by using 2-D finite element analysis (FEA) software develop by JMAG designer ver 15.0. The geometry structure of the 12S-14P PMFSM design is 264 mm diameter and the permanent magnet total weight is approximately 2 kg. The results of the 2-D FEA simulation indicate that the open angle between each SegSta is 30 degree for uniformly flux distribution in each SegSta core. It is found that the amplitude difference for each U, V, W phase is approximately zero since at 30 degree the flux density is evenly distributed at stator core with concentrated winding. Overall, this paper contributes to the methodology for designing a segmental stator 12Slot-14Pole PMFSM..